Ultrasonographic diagnosis of hydronephrosis made by experimental obstruction via ureteric ligation in dogs - Canpolat, Ibrahim; Canpolat, Leyla; Dinç, Mehmet; Günay, Cihan; Durmuş, A. Said; Han, M. Cengiz (Scientific and Technical Research Council of Turkey, 1996)
In this study, experimental obstruction was made by left ureteric ligation in seventeen adult, healty dogs. Microscopic and ultrasonographic diagnosis were researched in hydronephrotic dogs that examined during a month. Following operation in early dogs, kidney's size was enhanced, only except three cases for a month (P<0.005). Dilatation of calyces and decrease echogenite was showed in early days. Dilatation of renal pelvis increasesingly enhanced in 3 by 5 days (P<0.005). Kidneys echogenite decreased and anechoic fluid imaged. By fifth days, kidney lenghts was exceed to 9 cm. cortex and medullar atrophy was observed (P<0.005). Microscopically, there was no significant morphological changes in early days. After the following 5 days, increasingly enhanced dilatation of renal tubules and renal pelvis, hiperemia in tubular lumen were occured. This apperance was severed from 10 to 20 days, renal paranchyme atrophied from 20 to 30 days. This complete loss of renal paranchyma was occured at the end of 60 days.
Köpeklerde Üreterin Obstruksiyonuyla Deneysel Olarak Oluşturulan Hidronefrozisin Ultrasonografik Tanisi
Keywords: Dog; Hydronephrosis; Ultrasonography